Mary Poppins - Sherman, Richard M. 1928-2024; Sherman, Robert B. 1925-2012 (Walt Disney Home Entertainment, 2004)
After a banker's children lose their nanny due to her frustration with them, a change in the wind blows in a magical nanny who matches the children's qualifications, but not those of their very proper father. As Mary Poppins helps the children magically explore the world around them, their father grows increasingly disapproving of her methods, and he must eventually deal with his own distance from his children